THE CONSTITUTIONAL AND LEGAL STATUS OF REFUGEES IN THE REPUBLIC OF ARMENIA - Davtyan, Vahe; Gevorgyan, Anushik (Crisis Management and Technologies, 2025)
The article examines the constitutional and legal status of refugees in the Republic of Armenia. It analyzes the fundamental human rights and freedoms guaranteed by the Constitution of Armenia, as well as the rights of foreign nationals and stateless persons. The paper interprets the challenges related to the integration and naturalization of refugees in Armenia and evaluates the state's obligations in addressing refugee issues and promoting their integration.